Quality assessment of available Internet information on early orthodontic treatment - Mehmed Taha Alpaydin; Tugce Alpaydin; Merve Koklu; Suleyman Kutalmış Buyuk (BMC, 2024)
Abstract Background This study aimed to evaluate the content, reliability, quality and readability of information on Internet websites about early orthodontic treatment. Methods The "early orthodontic treatment" search term was individually entered into four web search engines. The content quality and reliability were reviewed with DISCERN, Journal of American Medical Association (JAMA), and Health on the Net code (HONcode) tools using the contents of websites meeting predetermined criteria. The readability of websites was evaluated with Flesch Reading Facilitate Score (FRES) and Flesch-Kincaid Grade Level (FKGL). Results Eighty-six websites were suitable for inclusion and scoring of the 200 websites. 80.2% of websites belonged to orthodontists, 15.1% to multidisciplinary dental clinics and 4.7% to professional organizations. The mean DISCERN score of all websites (parts 1 and 2) was 27.98/75, ranging between 19 and 67. Professional organization websites had the highest scores for DISCERN criteria. Moreover, 45.3% of websites were compatible with JAMA's disclosure criterion, 7% with the currency criterion, 5.8% with the authorship criterion and 5.8% with the attribution criterion. Only three websites met all JAMA criteria, and these websites belonged to professional organizations. None of the websites had the HONcode logo. Mean FRES and FKGL were 47.6 and 11.6, respectively. Conclusions The quality of web-based information about early orthodontic treatment is poor, and readability is insufficient. More accurate and higher quality Internet sources are required on the web.